Biofuel production from Nannochloropsis oculata microalgae in seawater without harvesting and dewatering over alumina-silicate supported nickel catalysts. (September 2018) - Deliismail, Ozgun; Ozdogru, Bertan; Seker, Erol
Abstract: The aim of this work was to study the production of biofuels from marine Nannochloropsis oculata without harvesting and dewatering over the single step sol-gel made alumina-silicate supported nickel catalysts at 80 °C and 1.0 atm. Sulfuric acid, hydrochloric acid, and nitric acid were used in the sol-gel to study the effect of acid type on catalyst activities. The catalyst made using sulfuric acid resulted in 74% microalgae conversion as compared to the catalysts made with other acids. Treatment of this catalyst with 35 g of NaCl per kg of water at 80 °C and 1.0 atm for 24 h increased microalgae conversion to 91.5% under the same reaction condition and the bio-fuels ranging from mono/polysaccharides, polyols to esters and fatty acids were produced. This study showed that nickel and 25.1 μmol/g of total acidity and acidic strength having 130–380 °C of temperature range was necessary to achieve 91.5% conversion. Highlights: Biofuels from marine N. oculata on solid catalysts without harvesting and dewatering Higher biofuel production on NaCl treated and untreated catalysts at 80 °C and 1 atm Highly active catalysts with moderate acidity/acidic strength and presence of nickel